ANALISIS PENGARUH FAKTOR SITUASIONAL TERHADAP KEPUTUSAN MASYARAKAT MENABUNG DI BANK SYARIAH KOTA MEDAN - Nurul Inayah (Studia Economica : Jurnal Ekonomi Islam, 2021)
Saving is an activity to set aside some of the money they have to keep. People's decision to save occurs based on internal factors, external factors and situational factors. The research was aimed to analyze the customer’s saving decision at sharia bank based on situational factors. This study uses a quantitative approach with Multiple Linear Regression analysis using Eviews version 8 software. The results show that there is a relationship between bank services on saving decisions and bank physical objects on saving decisions if partially reviewed. Likewise, it is also examined simultaneously the influence of bank services and bank physical objects on saving decisions. Therefore, improving services and the availability of convenient physical object facilities by banks is highly recommended to increase the interest and motivation to save the public. This can be a step to accelerate marketing for Islamic banks in increasing the number of customers.